Septins and Bacterial Infection - Torraca, Vincenzo; Mostowy, Serge (Frontiers in Cell and Developmental Biology, 2016)
Septins, a unique cytoskeletal component associated with cellular membranes, are increasingly recognized as having important roles in host defense against bacterial infection. A role for septins during invasion of Listeria monocytogenes into host cells was first proposed in 2002. Since then, work has shown that septins assemble in response to a wide variety of invasive bacterial pathogens, and septin assemblies can have different roles during the bacterial infection process. Here we review the interplay between septins and bacterial pathogens, highlighting septins as a structural determinant of host defense. We also discuss how investigation of septin assembly in response to bacterial infection can yield insight into basic cellular processes including phagocytosis, autophagy, and mitochondrial dynamics.